Identification of Common and Distinct Pathways in Inflammatory Bowel Disease and Colorectal Cancer: A Hypothesis Based on Weighted Gene Co-Expression Network Analysis - Derakhshani, Afshin; Javadrashid, Darya; Hemmat, Nima; Dufour, Antoine; Solimando, Antonio Giovanni; Abdoli Shadbad, Mahdi; Duijf, Pascal H. G.; Brunetti, Oronzo; Silvestris, Nicola; Baradaran, Behzad (Frontiers in Genetics, 2022)
Patients with inflammatory bowel disease (IBD), including ulcerative colitis and Crohn's disease, are at higher risks to develop colorectal cancer (CRC). However, the underlying mechanisms of this predisposition remain elusive. We performed in-depth comparative computational analyses to gain new insights, including weighted gene co-expression network analysis (WGCNA) and gene ontology and pathway enrichment analyses, using gene expression datasets from IBD and CRC patients. When individually comparing IBD and CRC to normal control samples, we identified clusters of highly correlated genes, differentially expressed genes, and module-trait associations specific for each disease. Once comparing IBD to CRC, we identified common hub genes and commonly enriched pathways. Most notably, IBD and CRC share significantly increased expression of 5 genes (MMP10, LCN2, REG1A, REG3A, and DUOX2), enriched inflammatory and neutrophil activation pathways most notable, highly significant enrichment of IL-4 and IL-13 signaling. Thus, our work expands our knowledge about the intricate relationship between IBD and CRC development and provides new rationales for developing novel therapeutic strategies.